Structure-property relationship and transport properties of structurally related silyl carbonate electrolytes. (10th August 2015) - Philipp, Manuela; Bhandary, Rajesh; Groche, Florian J.; Schönhoff, Monika; Rieger, Bernhard
Abstract: Ten different substituted structurally related linear and cyclic carbonates were synthesized and investigated as electrolyte solvents for lithium-ion cells. Synthesis of the compounds, mainly silyl carbonates, was carried out via catalytic CO2 addition, nucleophilic substitution or hydrosilylation. Besides the ten synthesized compounds a binary mixture of a cyclic and linear silyl carbonate, propylene carbonate (PC), diethyl carbonate (DEC) and a binary mixture thereof were analyzed as a function of molar lithium ((bistrifluoromethyl) sulfonyl) imide LiTFSI ratio in order to develop a structure-property relationship. The extrapolation of the temperature-dependent ionic conductivities using Vogel-Tamman-Fulcher (VTF) equation revealed a solvent assisted ionic transport mechanism. The strength of interaction between the lithium-ion and the respective carbonates was investigated via 13 C and 29 Si NMR measurements by the change of the chemical shift upon LiTFSI addition. The results show that the interaction of the lithium ion with the cyclic carbonates is much stronger compared to the linear ones and varies among the different substituents. These findings were in good accordance with ionicities represented by the Walden product. The diffusivities of Li + and TFSI − were determined via Pulsed Field Gradient STimulated Echo (PGSTE)-NMR. The hydrodynamic radii calculated thereof demonstrate the superior coordination ability of the cyclic carbonates as compared to linear structures. Furthermore, Haven ratios indicate rather different dissociation abilities of different carbonate solvents, depending on the structural fragment of the solvents.